Review: The Nutritional Management of Multiple Sclerosis With Propionate - Tobin, Derek; Vige, Runar; Calder, Philip C. (Frontiers in Immunology, 2021)
Over the last 15 years there has been an accumulation of data supporting the concept of a gut-brain axis whereby dysbiosis of the gut microbiota can impact neurological function. Such dysbiosis has been suggested as a possible environmental exposure triggering multiple sclerosis (MS). Dysbiosis has been consistently shown to result in a reduction in short-chain fatty acid (SCFA) producing bacteria and a reduction in stool and plasma levels of propionate has been shown for MS patients independent of disease stage and in different geographies. A wealth of evidence supports the action of propionate on T-cell activity, resulting in decreased T-helper cell 1 (Th1) and T-helper cell 17 (Th17) numbers/activity and increased regulatory T cell (Treg cell) numbers/activity and an overall anti-inflammatory profile. These different T-cell populations play various roles in the pathophysiology of MS. A recent clinical study in MS patients demonstrated that supplementation of propionate reduces the annual relapse rate and slows disease progression. This review discusses this data and the relevant mechanistic background and discusses whether taming of the overactive immune system in MS is likely to allow easier bacterial and viral infection.